SELF-ESTEEM AND NARCISSISM IN GENERATION Z WHO LIKE TO CREATE CONTENT ON THE TIKTOK APPLICATION - Ni Putu Sinta Dewi; Christiana Hari Soetjiningsih (Sean Institute, 2023)
This study aims to determine the significance of the relationship between self-esteem and narcissism. There were 157 participants in this study using a purposive sampling technique. The data collection method used is the RSES scale (Rosenberg Self Esteem Scale) from Rosenberg which has been tested for construct validity in Indonesia by Maroqi as a self-esteem scale and the Narcissistic Personality Inventory (NPI) scale compiled by Raskin and Terry as the narcissistic scale. The data analysis technique used is the Pearson product-moment correlation technique. From the results of data analysis, a correlation coefficient (r) was obtained -0.621 with a significance value of 0.000 (p<0.01), which means that there is a significant negative relationship between self-esteem and narcissism in Generation Z, who likes to create content on the TikTok application. This means that low self-esteem will be followed by high narcissism and vice versa if high self-esteem is followed by low narcissism.